2011
DOI: 10.3857/roj.2011.29.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Helical tomotherapy for spine oligometastases from gastrointestinal malignancies

Abstract: PurposeThis study evaluated the treatment effectiveness and proper radiation dose of helical tomotherapy (HT) in spine oligometastases from gastrointestinal cancers.Materials and MethodsFrom 2006 to 2010, 20 gastrointestinal cancer patients were treated with HT for spine oligometastases (31 spine lesions). The gross tumor volume (GTV) was the tumor evident from magnetic resonance imaging images fused with simulation computed tomography images. Clinical target volume (CTV) encompassed involved vertebral bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…To date, several studies described clinical features and radiotherapeutic strategies in HCC patients with bone metastasis, and many studies have evaluated stereotactic body RT for spine metastasis. [ 5 8 ] Unlike vertebral metastases, few studies have evaluated HCC patients with pelvic bone metastasis. The pelvic skeleton supports the balance of the trunk and has a complex bone anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies described clinical features and radiotherapeutic strategies in HCC patients with bone metastasis, and many studies have evaluated stereotactic body RT for spine metastasis. [ 5 8 ] Unlike vertebral metastases, few studies have evaluated HCC patients with pelvic bone metastasis. The pelvic skeleton supports the balance of the trunk and has a complex bone anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicities caused by HT and sliding window (SW)‐IMRT for oropharyngeal cancer were all low; however, toxicities associated with HT were less severe than those associated with SW‐IMRT (Table ). xii Spinal tumor/metastasis: the results of 4 observational studies ( n = 104) showed that, there was no severe toxicity associated with HT for spinal tumor/metastasis. The 1‐year survival rate was 67–73%, and the median and recurrence‐free median survival times were 5.1 months and 3 months, respectively; and the pain relief rate was 93.8% (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 145 original studies ( n = 6992) were included in the analysis (mainly including CCTs and observational studies) (Table ). Fourteen types of cancer (82%) were assessed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…HT is a unique IMRT machine, with a different dose delivery and treatment plan prescription compared to conventional linear accelerators-based IMRT, enabling treatment implementation for a wide spectrum of clinical cases, ranging from very small tumor to vast target volumes [ 15 ]. A few studies of HT in patients with metastatic cancer have reported effectiveness with a symptom control rates of 76%-90% within a time frame as short as 6 months [ 16 17 18 ]. In terms of colorectal oligometastases, several studies have reported CR rates of 16%-35% and 1-year LPFS rates of 54%-87% after HT [ 11 19 20 21 ].…”
Section: Discussionmentioning
confidence: 99%